Personnel economics in practice - Lazear, Edward P. 1948-2020; Gibbs, Michael 1962- (Wiley, 2015)
"Economics is a methodology that has been applied to many areas of human behavior, and has had enormous influence on the study of organizations and human resources. Developed by much of the founding research from Edward Lazear, this economic approach in these areas adds rigor, structure, and clarifies many important issues.The goal of this text is to give the reader a rigorous framework for understanding organizational design and the management of employees. Not only will students learn and apply ideas from microeconomics, but they will also learn principles that will be valuable in their future careers"..